Democratic Deficit in the Governance of the Indonesian Capital City: Defisit Demokrasi dalam Tata Kelola Ibu Kota Nusantara - Rena Puspita Dewi Purba; Mayang Rabbani; Firli Novansyah Putra (Universitas Muhammadiyah Sidoarjo, 2026)
Background: The relocation of Indonesia’s national capital to East Kalimantan has introduced a distinctive governance arrangement for the administration of the Indonesian Capital City. Specific background: This arrangement is implemented through the Indonesian Capital Authority, a ministerial-level institution directly accountable to the President and operating outside the conventional regional government system. Knowledge gap: Limited legal scholarship has examined how this governance model aligns with good governance principles and democratic constitutional norms. Aims: This study analyzes the governance of the Indonesian Capital City by examining the position and authority of the Indonesian Capital Authority within the framework of good governance. Results: The findings show that the concentration of extensive administrative powers in the absence of a local representative body generates accountability gaps, weak public participation, and limited checks and balances. Novelty: This research conceptualizes the democratic deficit in the governance of the Indonesian Capital City through an administrative law and constitutional perspective. Implications: The study highlights the need for regulatory restructuring and oversight mechanisms to ensure transparent, accountable, and democratically grounded governance. Highlights The governance of the Indonesian Capital City is characterized by centralized authority. The absence of local representative institutions reflects a democratic deficit. Good governance principles are not fully reflected in the current governance structure. Keywords Indonesian Capital Authority, Good Governance, Democratic Deficit, Capital City Governance, Constitutional Administration